2010
DOI: 10.1039/b923465a
|View full text |Cite
|
Sign up to set email alerts
|

Invader LNA: Efficient targeting of short double stranded DNA

Abstract: Despite progress with triplex-forming oligonucleotides or helix-invading peptide nucleic acids (PNAs), there remains a need for probes facilitating sequence-unrestricted targeting of double stranded DNA (dsDNA) at physiologically relevant conditions. Invader LNA probes, i.e., DNA duplexes with "+1 interstrand zipper arrangements" of intercalator-functionalized 2'-amino-α-L-LNA monomers, are demonstrated herein to recognize short mixed sequence dsDNA targets. This approach, like pseudo-complementary PNA (pcPNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 59 publications
8
88
0
Order By: Relevance
“…Consistent with our previous observations with other Invader chemistries, 6,7,12,14,15 duplexes with +1 interstrand zippers of S monomers are less stable than probes with other zipper arrangements (compare T m 's for S2:S5 relative to other probe duplexes, Table 4). The energetically activated nature of S2:S5 was verified through analysis of thermodynamic parameters, which were obtained from denaturation curves.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our previous observations with other Invader chemistries, 6,7,12,14,15 duplexes with +1 interstrand zippers of S monomers are less stable than probes with other zipper arrangements (compare T m 's for S2:S5 relative to other probe duplexes, Table 4). The energetically activated nature of S2:S5 was verified through analysis of thermodynamic parameters, which were obtained from denaturation curves.…”
supporting
confidence: 91%
“…6,12-15 In the present work, we set out to study the influence of the 2′-heteroatom of the pyrene-functionalized nucleotide monomer on the dsDNA-recognition characteristics of Invader probes. We hypothesized that the lower electronegativity of the sulfur atom of 2′- S -(pyren-1-yl)methyl-2′-thiouridine monomer S would weaken the gauche effect between O4′ and the 2′-substituent, and thus increase the population of C2′- endo ( South -type) furanose conformations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Subsequent studies revealed that the synthetically more readily available 2′- O -(pyren-1-yl)methyl-RNA monomers can be used instead with minimal or no loss in dsDNA-recognition efficiency. 20 In fact, we have shown that Invader probes based on the 2′- O -(pyren-1-yl)methyl-RNA chemistry can be used for recognition of mixed-sequence chromosomal DNA targets at non-denaturing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 bottom). 16-22 We have previously used the stability difference between Invaders and probe-target duplexes to realize mixed-sequence recognition of linear dsDNA targets, 16,17 DNA hairpins 18,19 and chromosomal DNA. 18 …”
mentioning
confidence: 99%